The Psychometric Properties for the Test of Perceived Physical Competence for Youths with Visual Impairments. (September 2021) - Brian, Ali; Starrett, Angela; Ross, Robbie; Pennell, Adam; Gilbert, Emily; Miedema, Sally Taunton; Casner, Chandler; Lieberman, Lauren J.
Introduction: Limited inquiries exist for perceptions of physical competence for people with visual impairments, since there are no specific, psychometrically tested scales. The purpose of this study was to establish the psychometric properties of the Test of Perceived Physical Competence (TPPC) for individuals with visual impairments aged 9–19 years.Methods: Experts ( N = 12) provided feedback for content and face validity. Then, after assessing 179 individuals with visual impairments, McDonald's Omega, and Confirmatory Factor Analyses were used to evaluate the internal consistency and structure. Finally, results of the TPPC were compared with the Self-Perception Profiles for Children/Adolescents for divergent validity.Results: The standardized root mean square residual result of 0.053 and the Comparative Fit Index result of 0.95 indicated acceptable fit. The percent of variation in each item explained by the factor varied from 44% (item 3) to 63% (item 6). McDonald's Omega for the one-factor scale is 0.987, and the perceived physical competence subscale of the Self-Perception Profiles for Children and TPPC have a Spearman correlation coefficient of 0.469 (95% confidence interval = 0.269–0.630).Discussion: Having a psychometrically strong scale to measure perceived physical competence of individuals with visual impairments is the first step in being able to replicate current, seminal research among this unique population. This adaptation of Harter's perceived physical competence subscale uniquely assesses the child's perceptions of physical competence among peers with visual impairments. This measure, coupled with the power to examine its predictive abilities, is important for children and adolescents with visual impairments, since they possess great tendencies for obesity and sedentary behavior.Implications for practitioners: If practitioners would like to change tendencies for obesity and sedentary behavior, then, they must include perceptions of physical competence as a latent construct. Now, practitioners can feel confident to do so for this highly vulnerable population.